Experimental determination of the lateral resolution of surface electric potential measurements by Kelvin probe force microscopy using biased electrodes separated by a nanoscale gap and application to thin-film transistors. Issue 8 (22nd March 2022) - Brouillard, Mélanie; Bercu, Nicolas; Zschieschang, Ute; Simonetti, Olivier; Mittapalli, Rakesh; Klauk, Hagen; Giraudet, Louis
Abstract : The lateral resolution of a double-pass Kelvin probe force microscopy system is estimated using 12 nm gap electrodes. The electric fields at the source contact of organic thin film transistors fabricated by stencil or e-beam lithography are compared. Abstract : A method is proposed to estimate the lateral resolution of surface potential profile measurements using Kelvin probe force microscopy (KPFM) on operating electronic devices. De-embedding the measured profile from the system response is required for various applications, such as contact characterization of thin-film transistors, or local longitudinal electric field measurements. A method is developed based on the measurement of the electric potential profile of two metallic electrodes separated by a nano-gap, providing a quasi-planar configuration. The electrodes are independently biased so as to produce an abrupt and well-controlled potential step. This calibration sample is used to measure the system impulse response in various configurations. Due to the application constrains, the KPFM method employed here is based on a dual-pass mode, demonstrated to provide reliable measurements on operating electronic devices. The method is applied to two types of conductive AFM probes. Measurements are performed at different tip-to-sample heights allowing the determination of the lateral resolution of the double-pass method. Detailed description of the measurements and resolution results are given for the present KPFM configuration. The system resolution measurement technique can be extended to other KPFM modes and can be used to monitor the degradation of the tip quality during long measurement campaigns. Finally, the method is applied to the characterization of thin-film transistors, and the effects of contact edge sharpness on the device behavior is discussed. The longitudinal electric field responsible for charge injection at the source-contact edge is successfully estimated and compared for organic thin-film transistors fabricated by stencil lithography or electron-beam lithography.